MITOLOGI TENUN GEDOGAN INDRAMAYU: IDE DAN PROSES KONSTRUKSI WACANA - Dewi Mustikasari (ATRAT: Jurnal Seni Rupa, 2021)
The motifs of Babaran, Kluwungan, Poléng Méntisa, and Udan Mas Prambutan are the four motifs of Gedogan Indramayu weaving which are mythized by the user community as narratives of defense mechanisms for systems that have been practiced for a long time. In principle, a mythology is formed by the people themselves to gain their own knowledge in reading the phenomena of life and the natural surroundings. Mythology stems from the perception of the people who are arbitrary and connotative in deciphering the meanings of Gedogan Indramayu weaving. The connotation of believing and being believed together becomes a kind of collective 'faith'. The connotative perception is then uniformized and turned into a fixed and absolute rule or into a kind of convention. Furthermore, when testing the validity of the convention, it persists in its application in society, so that its predicate turns into a myth. Then this myth is also tested by time, survives in the community, reaches the side of a solid belief for the people, so that it becomes a system of thinking and living for the Juntikebon community. Keywords: Mythology, Weaving Gedogan Indramayu, Babaran, Kluwungan, Poléng Méntisa, Udan Mas Prambutan. -----------------------------------------------------------------------------------------Motif Babaran, Kluwungan, Poléng Méntisa, dan Udan Mas Prambutan adalah empat motif tenun Gedogan Indramayu yang dimitoskan oleh masyarakat penggunanya sebagai narasi mekanisme pertahanan bagi sistem-sistem yang telah dijalani sejak dulu. Pada prinsipnya, suatu mitologi dibentuk oleh masyarakatnya sendiri untuk mendapatkan pengetahuannya sendiri dalam membaca fenomena hidup dan alam sekitar. Mitologi bermula dari persepsi masyarakatnya yang arbiter dan konotatif dalam menguraikan makna-makna tenun Gedogan Indramayu. Konotasi itu dipercaya dan diyakini secara bersama-sama menjadi semacan ‘iman’ kolektif. Persepsi yang konotatif itu kemudian diseragamkan dan berubah menjadi suatu aturan yang tetap dan mutlak atau menjadi semacam konvensi. Selanjutnya, waktu menguji keberlakuan konvensi itu tetap bertahan dalam penerapannya di masyarakat, sehingga predikatnya berubah menjadi sebuah mitos. Kemudian mitos ini juga diuji oleh waktu, bertahan di masyarakatnya, mencapai pada sisi keyakinan yang mantap bagi masyarakatnya, hingga menjadi suatu sistem berpikir dan berkehidupan bagi masyarakat Juntikebon. Kata Kunci: Mitologi, Tenun Gedogan Indramayu, Babaran, Kluwungan, Poléng Méntisa, Udan Mas Prambutan.